Quality of life of patients undergoing chemotherapy: a tertiary care hospital-based study from Karachi - Junaid, Natalia; Khan, Muneeba; Uddin, Muhammad Roohan; Masroor, Agha Shehroz; Muhammad Sualeh; Ghulam Haider (Journal of the Pakistan Medical Association, 2024)
The quality of life (QoL) of cancer patients is of paramount concern due to the enduring effects of chemotherapy on the physical, emotional, spiritual, and social aspects of life. This study aims to examine the factors influencing QoL among cancer patients. A cross-sectional analysis encompassing 200 chemotherapy patients aged 18 and above was conducted, using self-reported surveys and clinical records. The results indicate higher social well-being and lower physical well-being scores. Significantly, patients in joint families, with income above Rs25,000, limited pre-diagnosis check-ups, over four chemotherapy cycles, showed better QoL. Engaging diversions like art and internet usage alleviated worries. Conversely, comorbidities correlated with lower FACT-G scores. QoL is still compromised, even with the developments of advanced cancer treatments. Managing mental, emotional, social, and physical health is vital. —Continue